Immersive Virtual Reality Storytelling to Enhance Speaking Fluency, Narrative Skills, and Engagement in Second Language Education - Aprin Wahyu Wijayanti; Maulia Depriya Kembara; Arjulayana Arjulayana (Global Education : International Journal of Educational Sciences and Languages, 2024)
This research explores the use of Virtual Reality (VR) storytelling in language learning, focusing on its impact on speaking fluency, narrative skills, and student engagement. As traditional language teaching methods often face challenges such as limited speaking practice and learner anxiety, VR offers a promising alternative by creating immersive, interactive environments that encourage active participation. The objective of the study was to investigate the effectiveness of VR storytelling in enhancing these language skills, particularly in second language learners. The study utilized an action research methodology, involving language learners who participated in VR-based storytelling interventions. Pre- and post-assessments, along with surveys and student feedback, were used to evaluate speaking fluency, narrative construction, and overall engagement. The findings indicated significant improvements in all three areas, with students reporting increased confidence, reduced anxiety, and enhanced motivation to engage with the language. The use of VR not only improved grammatical and lexical aspects of speaking but also fostered creativity and coherence in storytelling. These results support the potential of VR to transform traditional language education by providing an engaging, low-pressure environment for learners. The study concludes by recommending the integration of VR in language classrooms to enhance language acquisition and suggests further exploration into long-term effects and content diversity.